(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
The purpose of this paper is to evaluate the quality of the ILS library collection of the Faculty of Humanities and Social Sciences (FHSS) in Osijek, Croatia and its congruence with the curriculum. The quality of the collection is measured using the check-list method. The required and optional reading lists of the Department of Information Sciences at the FHSS (academic year 2011/2012) are used as standard lists that the library holdings are compared to. The results found that the library does not have 30.8 per cent of the titles on the reading lists. The remaining 33.9 per cent of the titles are accessible in the library, 28.5 per cent are free electronic resources, and 6.8 per cent of titles are accessible for students through the Department’s Moodle, Learning Management System. The study provides data about the titles available and not available in the FHSS library. However, it does not differentiate between the titles on the required and optional reading lists. This study provides the FHSS librarians with the list of titles that should be obtained in the near future. In Croatia, very few papers on collection assessment have been published so far, and this is the first study about the quality of a library collection at the University of Osijek. The paper attempts to fill that gap and contribute to a deeper understanding of the quality of library collections in the Croatian academic setting.